In Vitro Characterization of the Pharmacological Properties of the Anti-Cancer Chelator, Bp4eT, and Its Phase I Metabolites - Potůčková, Eliška; Roh, Jaroslav; Macháček, Miloslav; Sahni, Sumit; Stariat, Ján; Šesták, Vít; Jansová, Hana; Hašková, Pavlína; Jirkovská, Anna; Vávrová, Kateřina; Kovaříková, Petra; Kalinowski, Danuta S; et al. (PloS one, 2015)
Cancer cells have a high iron requirement and many experimental studies, as well as clinical trials, have demonstrated that iron chelators are potential anti-cancer agents. The ligand, 2-benzoylpyridine 4-ethyl-3-thiosemicarbazone (Bp4eT), demonstrates both potent anti-neoplastic and anti-retroviral properties. In this study, Bp4eT and its recently identified amidrazone and semicarbazone metabolites were examined and compared with respect to their anti-proliferative activity towards cancer cells (HL-60 human promyelocytic leukemia, MCF-7 human breast adenocarcinoma, HCT116 human colon carcinoma and A549 human lung adenocarcinoma), non-cancerous cells (H9c2 neonatal rat-derived cardiomyoblasts and 3T3 mouse embryo fibroblasts) and their interaction with intracellular iron pools. Bp4eT was demonstrated to be a highly potent and selective anti-neoplastic agent that induces S phase cell cycle arrest, mitochondrial depolarization and apoptosis in MCF-7 cells. Both semicarbazone and amidrazone metabolites showed at least a 300-fold decrease in cytotoxic activity than Bp4eT towards both cancer and normal cell lines. The metabolites also lost the ability to: (1) promote the redox cycling of iron; (2) bind and mobilize iron from labile intracellular pools; and (3) prevent 59Fe uptake from 59Fe-labeled transferrin by MCF-7 cells. Hence, this study demonstrates that the highly active ligand, Bp4eT, is metabolized to non-toxic and pharmacologically inactive analogs, which most likely contribute to its favorable pharmacological profile. These findings are important for the further development of this drug candidate and contribute to the understanding of the structure-activity relationships of these agents.
Keywords: Mitochondria; Cell Line; protinádorové látky; Cell Line, Tumor; S Phase Cell Cycle Checkpoints; Cell Proliferation; reaktivní formy kyslíku; Thiosemicarbazones; železo; Iron Chelating Agents; chelátory železa; Cell Death; buněčná smrt; oxidace-redukce; Reactive Oxygen Species; semikarbazony; lidé; Iron; Humans; metabolické sítě a dráhy; buněčné linie; proliferace buněk; Semicarbazones; nádorové buněčné linie; Oxidation-Reduction; kontrolní body fáze S buněčného cyklu; thiosemikarbazony; Metabolic Networks and Pathways; mitochondrie; Antineoplastic Agents